Analysis of Decision Number 172 K/Pdt.Sus-Hki/2024 in the IPR Dispute Between Jollibee Foods Corporation and PT Tatalogam Lestari - Tuasikal, Naisyirah Ramadhani (CV. Rayyan Dwi Bharata, 2024)
The Supreme Court of the Republic of Indonesia in cassation case Number 172 K/Pdt.Sus-HKI/2024 provided in-depth legal considerations regarding the trademark dispute between JOLLIBEE FOODS CORPORATION and PT Tatalogam Lestari. This decision confirms that the